2018
DOI: 10.1002/jcb.27477
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐1β/nuclear factor‐κB signaling promotes osteosarcoma cell growth through the microRNA‐181b/phosphatase and tensin homolog axis

Abstract: So far, microRNA has attracted plenty of interest due to its role in tumorigenesis. Reportedly, miR‐181b may be involved in the tumorigenesis of osteosarcoma (OS). In the current study, we attempted to investigate the detailed function and mechanism of miR‐181b in OS carcinogenesis. Herein, miR‐181a, miR‐181b, miR‐181c, and miR‐181d expressions in OS tissues were higher than that in nontumor tissue samples as examined real‐time polymerase chain reaction. Via direct targeting, miR‐181b negatively regulated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…IL-1β induces the expression of miR-425, miR-181a, and miR-181b through NF-κB, in gastric cancer, colon cancer, and osteosarcoma cells, respectively. These miRNA repress PTEN expression, leading to apoptosis inhibition and proliferation-associated cancer cell growth [ 74 , 116 , 117 ]. PTEN expression in myeloid cells dictates NLRP3 inflammasome activation and IL-1β expression.…”
Section: Pro-and Anti-tumor Effects Of Il-1βmentioning
confidence: 99%
“…IL-1β induces the expression of miR-425, miR-181a, and miR-181b through NF-κB, in gastric cancer, colon cancer, and osteosarcoma cells, respectively. These miRNA repress PTEN expression, leading to apoptosis inhibition and proliferation-associated cancer cell growth [ 74 , 116 , 117 ]. PTEN expression in myeloid cells dictates NLRP3 inflammasome activation and IL-1β expression.…”
Section: Pro-and Anti-tumor Effects Of Il-1βmentioning
confidence: 99%
“…Although miR‐181a and miR‐181b expressions were detected in PAH animal models, further studies with clinical samples could better elucidate the correlation of miR‐181a/b expression with PAH. It is broadly reported that miR‐181a and miR‐181b can also target multiple genes, like PTEN, to mediate the regulation of various pathological processes (W. Wang et al, ; X. F. Wu, Zhou, & Zou, ). In the meanwhile, previous studies have indicated the implications of PTEN in pulmonary vascular remodeling (Nemenoff et al, ; Ravi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The role of IL-1β and Wnt signaling has also been implicated in the bone metastatic growth of breast cancer [21], which will be discussed in the section dedicated to the IL-1 family in bone metastasis. In OS cell lines, IL-1β, through the induction of NF-κB, also upregulates miR-181b expression, which, by repressing phosphatase and tensin homolog (PTEN) expression, promotes OS cell proliferation [42]. Additionally, IL-1β has been implicated in OS drug resistance.…”
Section: Il-1 Family In Osteosarcomamentioning
confidence: 99%